PARTISIPASI LEMBAGA SWADAYA MASYARAKAT DALAM MENGONTROL PRAKTEK POLITIK UANG PADA PEMILIHAN LANGSUNG KEPALA DAERAH - Solehoddin, Sirajuddin dan (Jurnal Konstitusi, 2010)
To control money politics occuring in the direct election of local leaders, there are four forms of participation the non-governmental organizations in Malang regency can take, namely: firstly, making studies and holding discussions and also coalition to unite various parties in order to eliminate money politic, so a good gorvernance is created: secondly, giving political education to the people in order to build their maturity and awareness on the importance of just general election and good governance; thirdly, making direct monitoring on the implementation of direct election of the local leader and fourthly, giving pressure to the local government and the local house of representative to create good governance consistently and seriously.